Respuesta :

Answer:

A3-a-c=b assuming you mean A=[tex]\frac{a+b+c}{3}[/tex]

Step-by-step explanation:

Basically, we'll be using properties of equalities to "balence out the equation" and shift all variables except for b to one side

1) Use multiplication prop. of equality

This property states that if we multiply one side we must multiply the other. We'll be doing this for the "3" portion.

3(A)=3((a+b+c)/3)

3A= a+b+c

2) Use subtraction prop of equality

This one states that if we subtract one side we must subtract the other. We will be doing this for the "a" and "c" portion

(3A)-a=(a+b+c)-a

3A-a=b+c

(3A-a)-c=(b+c)-c

3A-a-c=b

Hopefully that helps a bit T_T

Answer:[tex]b=A-a-\frac{c}{3}[/tex]

Step-by-step explanation:

The answer to the question is really simple. In question where they ask you to solve for a variable with unknown values, they are asking you to rearrange the equation to make that variable alone.

To demonstrate let's make b alone on one side:

[tex]A=a+b+\frac{c}{3}[/tex]

[tex]A-a=b+\frac{c}{3}[/tex]

[tex]A-a-\frac{c}{3}=b[/tex]

[tex]b=A-a-\frac{c}{3}[/tex]

Your final answer would be [tex]b=A-a-\frac{c}{3}[/tex]. This may seems like an invalid answer but the value of be will be equal to [tex]A-a-\frac{c}{3}[/tex], if you were given the value of the unknown variables.

ACCESS MORE